IMPLEMENTASI HASIL ANALISIS RAPORT PENDIDIKAN DAN OBSERVASI KELAS DALAM MENYUSUN PERENCANAAN BERBASIS DATA DI TASIKMALAYA - ZM, Endang; Warisno, A; Siti, Patimah; Arafah, A Latief Arung (FIKRAH, 2024)
This research aims to describe the implementation of the results of analysis of educational report cards and classroom observations in preparing Data Based Planning (PBD) at SMKN 3 Tasikmalaya, Tasikmalaya City, West Java Province. The focus is to assess the integration of findings from education report cards into school budget work plans (RKAS). A qualitative descriptive method was used, with data collected through interviews, observation and documentation. The results show that although SMKN 3 Tasikmalaya has identified problems through education report cards, the integration of the findings into the RKAS has not been effective. Budget allocations do not fully address identified needs, such as improving reading and math skills and improving the school safety climate. Recommendations include improving RKAS preparation through systematic planning, deeper data analysis, and stakeholder involvement. This study emphasizes the importance of data integration in education management and provides recommendations for improving the quality of education through better financial management.